1984
DOI: 10.1111/j.1365-2222.1984.tb02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of sodium cromoglycate by pressurized aerosol

Abstract: Summary Sodium cromoglycate (SCG) has recently been formulated as a pressurized aerosol. Twenty‐five asthmatic outpatients taking SCG via the Spinhaler were studied in a double‐dummy, double‐blind cross‐over trial in which subjects took Spincaps containing 20 mg of SCG for 2 months, and for the alternate 2 months were treated with SCG aerosol delivering 1 mg/actuation. There was no evidence of clinical deterioration occurring during the period on aerosol SCG. During this period however cough frequency was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Other preparations of sodium cromoglycate. Recent studies with aqueous SCG have suggested that 2 mg administered by pressurized aerosol is as good as 20 mg of dry powder in adults and chilren, provided good aerosol inhalation technique is employed [42]. However it must be emphasized that inhalation techniques are equally critical with the dry powder inhaler, and many treatment failures are due to inadequate use of the devices.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Other preparations of sodium cromoglycate. Recent studies with aqueous SCG have suggested that 2 mg administered by pressurized aerosol is as good as 20 mg of dry powder in adults and chilren, provided good aerosol inhalation technique is employed [42]. However it must be emphasized that inhalation techniques are equally critical with the dry powder inhaler, and many treatment failures are due to inadequate use of the devices.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In intersti tial cystitis, characterized as severe and chronic type allergic cystitis, the bladder is comprised of abundant mast cells and a high histamine content [27], According to previous investigators [13,29], eosinophil appears to act commonly in the resolution of inflammation by sup pressing histamine and the slow-reacting anaphylaxis substance. In mast cell degranulation studies the prohibi tive action of Tranilast was similar to that of disodium cromoglycate [17] which inhibits reaginic antibody-me diated hypersensitivity reactions [1,5,19,23], The authors postulated that some metabolites of this agent might have been condensed in urine. Subsequently an allergic reaction results in the bladder wall instead of inhibiting reaginic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of trials comparing the effects of the 1 mg metered dose inhaler (2 x 1 mg qds) and the dry powder Spincaps® (20 mg qds). In most studies patients stabilized on the dry powder formulation of sodium cromoglycate were transferred to the metered dose inhaler form without loss of effect [104][105][106][107]. In addition there have been a number of studies comparing the efficacy ofthe 1 mg aerosol with a placebo preparation in adult patients [I08-110] and in children [11N113] (Fig.…”
Section: Intal® Metered Dose Inhalersmentioning
confidence: 99%